New records of phytoplankton for Bangladesh. 4. Chlorococcales - Khondker, Moniruzzaman; Bhuiyan, Rauf Ahmed; Yeasim, Jenat; Alam, Munirul; Sack, R Bradley; Huq, Anwar; Colwell, Rita (Bangladesh Journal of Plant Taxonomy, 2008)
This study presents three species from each of Schroederia, Monoraphidium and Ankistrodesmus, two species and one variety of Dictyosphaerium, two varieties of Pediastrum, and Tetraedron arthrodesmiforme var. contorta, Chlorotetraedron polymorphum, Myrmecia aquatica, Oocystis tainoensis, Nephrocytium spirale, Kirchneriella irregularis, Coelastrum indicum and Scenedesmus similagineus. These taxa have been reported from some ponds of Mathbaria of Pirojpur and Bakerganj of Barisal Districts in Bangladesh. Key words: Chlorococcales, New records, Phytoplankton, Ponds DOI: 10.3329/bjpt.v14i2.528 Bangladesh J. Plant Taxon. 14(2): 83-91, 2007 (December)